Juxtacortical Clavicular Chondrosarcoma: Diagnostic Dilemmas: Case Report and Review of Literature - Efremidou, E.I. (Libertas Academica, 2013)
Juxtacortical chondrosarcoma is a rare primary malignant cartilaginous tumor accounting for 0.2% of all bone tumors. Wide surgical resection is the treatment of choice for juxtacortical chondrosarcomas. Accurate preoperative diagnosis is important in ensuring appropriate management, staging, and treatment of the patient. A combination of radiographs, three-dimensional imaging with computerized tomography (CT) scan and magnetic resonance imaging (MRI) can typically allow accurate diagnosis of juxtacortical chondrosarcomas. Bone scan and chest x-ray or CT chest scans are indicated for appropriate staging of the patient. Pet scan, ultrasound, bone scan, etc. are not typically needed for the diagnosis. Certainly, pulmonary imaging and bone scan are required for staging and could be commented upon.